Lightweight rotor design by optimal spar cap offset. Issue 6 (September 2016) - Croce, A; Sartori, L; Lunghini, M S; Clozza, L; Bortolotti, P; Bottasso, C L
Abstract: Bend-twist coupling behavior is induced in a blade by displacing the suction side spar cap towards the leading edge, and the pressure side one in the opposite direction. Additional couplings are introduced by rotating the spar cap fibers. The structural configuration of the blade is optimized using an automated design environment. The resulting blade shows significant benefits in terms of mass and loads when compared to the baseline uncoupled one. Finally, the lightweight design concept is used to increase the rotor size, resulting in a larger energy yield for the same hub loads.